Dinamika Industri Garam di Madura 1950-1975 - Rahayu Hardita Dwi Widyanti; Ponco Setiyonugroho (KARMAWIBANGGA: Historical Studies Journal, 2022)
Madura Island has been known for a long time as a salt-producing island. The salt industry in Madura is known to have started in the 19th century. Under the salt monopoly policy imposed by the Dutch Colonial Government, the welfare of salt farmers has increased. After Indonesia's independence, the euphoria of freedom and nationalism colored almost all regions in Indonesia, including Madura Island. As an island that was known to be quite productive during the Dutch Colonial Government, Madura became one of the islands that the Government of Indonesia fought for. The existence of a Salt Company owned by the Dutch Colonial Government was one of the main causes. The purpose of this study was to determine the dynamics of the salt industry in Madura after Indonesia's independence in 1950-1975. This Article show that under the Indonesian government, the salt industry in Madura actually experienced a decline.